The Use of Weblogs in Spanish Mainstream Media - Palomo Torres, Maria; Meso Ayerdi, Koldo (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
In this paper we aim to draw a picture of what is happening nowadays in Spanish mainstream cybermedia from the point of view of new ways of participation and, more concretely, we analyze remarkable weblogs signed by journalists and/or guests, in order to determine the author’s profile. A survey answered by 50 per cent of these bloggers let us know why the use of weblogs represents the key to media success in the online sphere.